Donor to recipient transmission of SARS‐CoV‐2 by lung transplantation despite negative donor upper respiratory tract testing. Issue 8 (15th March 2021) - Kaul, Daniel R.; Valesano, Andrew L.; Petrie, Joshua G.; Sagana, Rommel; Lyu, Dennis; Lin, Jules; Stoneman, Emily; Smith, Lane M.; Lephart, Paul; Lauring, Adam S.
Abstract: We describe a case of proven transmission of SARS‐CoV‐2 from lung donor to recipient. The donor had no clinical history or findings suggestive of infection with SARS‐CoV‐2 and tested negative by reverse transcriptase polymerase chain reaction (RT‐PCR) on a nasopharyngeal (NP) swab obtained within 48 h of procurement. Lower respiratory tract testing was not performed. The recipient developed fever, hypotension, and pulmonary infiltrates on posttransplant day (PTD) 3, and RT‐PCR testing for SARS‐CoV‐2 on an NP swab specimen was non‐reactive, but positive on bronchoalveolar lavage (BAL) fluid. One thoracic surgeon present during the transplantation procedure developed COVID‐19. Sequence analysis of isolates from donor BAL fluid (obtained at procurement), the recipient, and the infected thoracic surgeon proved donor origin of recipient and health‐care worker (HCW) infection. No other organs were procured from this donor. Transplant centers and organ procurement organizations should perform SARS‐CoV‐2 testing of lower respiratory tract specimens from potential lung donors, and consider enhanced personal protective equipment for HCWs involved in lung procurement and transplantation. Abstract : This report describes a proven case of SARS‐CoV‐2 transmission during lung transplantation from a deceased donor to both the recipient and to a healthcare worker. La Hoz et al. comment on page 2635 .